Idiosyncratic Jump Risk Matters: Evidence from Equity Returns and Options - Bégin, Jean-François; Dorion, Christian; Gauthier, Geneviève (Review of Financial Studies, 2020)
Abstract The recent literature provides conflicting empirical evidence about the pricing of idiosyncratic risk. This paper sheds new light on the matter by exploiting the richness of option data. First, we find that idiosyncratic risk explains 28% of the variation in the risk premium on a stock. Second, we show that the contribution of idiosyncratic risk to the equity premium arises exclusively from jump risk. Third, we document that the commonality in idiosyncratic tail risk is much stronger than that in total idiosyncratic risk documented in the literature. Tail risk thus plays a central role in the pricing of idiosyncratic risk. Received May 15, 2017; editorial decision September 12, 2018 by Editor Stijn Van Nieuwerburgh. Authors have furnished code and an Internet Appendix, which are available on the Oxford University PressWeb site next to the link to the final published paper online.